Evaluation of the Effects of Systemic Irisin Application on Guided Bone Regeneration in Peri-implant Bone Defects - Bulmus, Ozgur; Dundar, Serkan; Bozoglan, Alihan; Artas, Gokhan; Kirtay, Mustafa; Canpolat, Sinan (Lippincott Williams & Wilkins, 2022)
This study aimed to investigate the effects of systemic irisin hormone application on new bone formation in peri-implant bone defects. After surgically creating peri-implant bone defects in the metaphyseal part of the tibiae of rats, the rats were randomly divided into 2 equal groups: a control group and an irisin group. In the control group, the rats received no further treatment during the 4-week experimental period after the surgery. The rats in the irisin group, 100 ng/kg irisin was administered intraperitoneally 3 days a week during the 8 weeks experimental period after the surgery. At the end of the experimental period, the rats were euthanized. Implants and surrounding bone tissues were collected for histological new bone formation analysis. The Student t test was used for statistical analysis. There were no significant differences between the groups in the histological analysis, new bone formation and fibrosis (P>0.05). Also, in the irisin group, there was numerically but not statistically more new bone formation detected compared with the controls. Within the limitations of this study, irisin did not affect new bone formation in peri-implant defects, although the numerical values favored the irisin group.
Keywords: Bone; dental implants; guided bone regeneration; irisin; peri-implant bone regeneration